Injuries to the shoulder in the throwing athlete. Part one: Biomechanics/pathophysiology/classification of injury - Meister, K. (The American Journal of Sports Medicine, 2000)
Over the last decade, significant advances have been made in the study and understanding of shoulder mechanics. Much of this may be attributed to the use of more sophisticated technology to improve our ability to assess the shoulder in real-time athletics. As a consequence of these advances, our understanding of the pathophysiology of injury has also increased. Our manual examination skills have improved and our noninvasive diagnostic techniques have advanced greatly. New insight into forces at play during actions as complex as the throwing motion has allowed us to develop better protocols for the prevention and treatment of the most common injuries. Additionally, paralleling improvements in the understanding of shoulder kinematics and the pathophysiology of injury, advances in surgical techniques, particularly arthroscopy, have aided in the diagnosis of and the development of less invasive surgical treatments for injuries that do not respond to nonoperative measures. Undoubtedly, an up-to-date understanding of the developments in shoulder biomechanics, pathophysiology of injury, diagnostic techniques, and surgical management is necessary for the clinician who wishes to continue to apply proper skills in the sports medicine setting.